Towards virtuous and ethical organisational performance in the context of corruption: A case study in the public sector. (9th June 2020) - Fernando, Mario; Bandara, Ruwan
Summary: With the increasing number of ethical violations reported across the public sector, the emphasis on ethics and values in governance is on the rise. Corruption is widely accepted as a form of unethical behaviour that can have detrimental effects on organisations as well as society at large. Research calls for empirical studies focusing on the contextual factors surrounding corruption. Based on the Contextually Based Human Resource Theory and using the case study method, this paper examines the role of context through a systematic analysis of corruption in a public sector organisation. We integrate corruption and human resource literature to understand employee behaviour, employee relations, HRM strategies, and organisational outcomes in the context of organisational corruption.